Candesartan inhibits inflammation through an angiotensin II type 1 receptor independent way in human embryonic kidney epithelial cells - YU,YING (2019)
Abstract: Besides stimulating vasoconstriction, Angiotensin II is also well known in inducing reactive oxygen species and promoting inflammatory phenotype switch via its type 1 receptor. In clinic, Angiotensin II type 1 (AT1) receptor blocker like candesartan has been widely applied as an antihypertensive medication. We previous have demonstrated that a higher dose of candesartan plays a protective role after kidney injury. However, whether candesartan could exhibit anti-inflammatory effects remains unclear. Here, by stimulating isolated human embryonic kidney epithelial cells with tumor necrosis factor-α (TNF-α), we observed the anti-inflammation capacity of candesartan ex vivo. It was found that pre-treat with candesartan significantly suppressed transforming growth factor-β (TGF-β) and interleukin-6 (IL-6) expression after incubation with TNF-α. Surprisingly, silence of angiotensin II type 1 receptor has little effects on reducing TGF-β or IL-6 products. Furthermore, candesartan inhibited TNF-α-induced oxidative stress in the primary cultured tubular epithelial cells. Overall, our data indicates that candesartan suppresses TNF-α-induced inflammatory cytokine production by inhibiting oxidative stress, rather than block AT1 receptor activity.